A combinatorial study of substar reliability of the star network. (8th December 2008) - Palaniappan, Venka; Latifi, Shahram
Hierarchical networks may be divided into subnetworks having the same topological properties of the original network. The star graph, an example of hierarchical networks, has been studied extensively as a viable candidate for massively parallel systems. For a given number of faulty links and using a combinatorial approach, lower bounds on probability of having one or more (n − 1)-stars in an n-star are determined. An identification algorithm is presented to find an available (n − 1)-star in an n-star containing a set of faulty links.